Deletion of Glu155 causes a deficiency of glutathione transferase Omega 1-1 but does not alter sensitivity to arsenic trioxide and other cytotoxic drugs - Schmuck, Erica; Cappello, Jean; Coggan, Marjorie; Brew, Jenny; Cavanaugh, Juleen A.; Blackburn, Anneke C.; Baker, Rohan T.; Eyre, Helen J.; Sutherland, Grant R.; Board, Philip G. (The international journal of biochemistry & cell biology, 2008)
The Omega class glutathione transferase GSTO1-1 can catalyze the reduction of pentavalent methylated arsenic species and is responsible for the biotransfomation of potentially toxic α-haloketones. We investigated the cause of GSTO1-1 deficiency in the T-47D breast cancer cell line and found that the cell line is hemizygous for a polymorphic allele that encodes the deletion of Glu155. Northern and Western blots show that T-47D cells contain GSTO1 mRNA but no GSTO1-1 protein suggesting that the deletion of Glu155 causes GSTO1-1 deficiency in vivo. In further support of this contention we found that lymphoblastoid cell lines from subjects who are heterozygous for the deletion of Glu155 have only 60% of normal activity with the GSTO1-1 specific substrate 4-nitrophenacyl glutathione. Pulse-chase studies showed that the deletion of Glu155 causes increased turnover of GSTO1-1 in T47-D cells. These data establish the fact that the polymorphic deletion of Glu155 can cause GSTO1-1 deficiency in vivo. GSTO1-1 expression is elevated in some cell lines that are resistant to the cytotoxic cancer drugs adriamycin, etoposide and cisplatinum but its specific contribution to multi drug resistance has not been evaluated. In this study GSTO1-1 deficient T47-D cells were used to determine if GSTO1-1 contributes directly to arsenic and drug resistance. We established stable expression of normal GSTO1-1 in T-47D cells and found that this did not alter sensitivity to arsenic trioxide, cisplatinum daunorubicin or etoposide.